2021
DOI: 10.1007/s40744-020-00271-y
|View full text |Cite
|
Sign up to set email alerts
|

Disease Burden and Costs in Moderate-to-Severe Chronic Osteoarthritis Pain Refractory to Standard of Care: Ancillary Analysis of the OPIOIDS Real-World Study

Abstract: Introduction To determine the disease burden and costs in moderate-to-severe chronic osteoarthritis (OA) pain refractory to standard-of-care treatment in the Spanish National Health System (NHS). Methods Ancillary analysis of the OPIOIDS real-world, non-interventional, retrospective, 4-year longitudinal study including patients aged at least 18 years with moderate-to-severe chronic OA pain refractory to standard-of-care with sequential NSAIDs plus opioids. Burden assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…This was significantly higher than for patients in the control cohorts and consistent with our findings for higher HCRU and analgesic use. Many other studies have demonstrated the high cost of OA to healthcare systems, particularly for the management of patients with moderate to severe or severe pain [ 13 , 15 – 17 , 19 , 22 , 24 , 27 , 39 , 48 ]. Our multivariable analysis showed that older age at index or the presence of gout, osteoporosis, type 2 diabetes, or coronary artery disease was associated with an increased cost of healthcare in all cohorts, but with generally higher proportional contributions in control cohorts than the OA pain cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This was significantly higher than for patients in the control cohorts and consistent with our findings for higher HCRU and analgesic use. Many other studies have demonstrated the high cost of OA to healthcare systems, particularly for the management of patients with moderate to severe or severe pain [ 13 , 15 – 17 , 19 , 22 , 24 , 27 , 39 , 48 ]. Our multivariable analysis showed that older age at index or the presence of gout, osteoporosis, type 2 diabetes, or coronary artery disease was associated with an increased cost of healthcare in all cohorts, but with generally higher proportional contributions in control cohorts than the OA pain cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Particularly worrisome is the excess mortality associated with opioid use as described in the scientific literature, [45][46][47][48] mainly with strong opioids, which has also been observed in Spanish OA patients receiving strong opioids in the OPIOIDS study. 31,33 (A) (B) We used a real-world approach to project the future opioid burden for OA, based on recent opioid dispensing trends by the AEMPS, anticipated growth in the OA population and the opioid utilization rates observed in the real-world OPIOIDS study. 30,31,33 By assuming no change in opioid prescribing practices, our study provides an important baseline for health decision makers and clinicians in Spain, in order to evaluate the potential impacts of future strategies that aim to address inappropriate opioid prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…31,33 (A) (B) We used a real-world approach to project the future opioid burden for OA, based on recent opioid dispensing trends by the AEMPS, anticipated growth in the OA population and the opioid utilization rates observed in the real-world OPIOIDS study. 30,31,33 By assuming no change in opioid prescribing practices, our study provides an important baseline for health decision makers and clinicians in Spain, in order to evaluate the potential impacts of future strategies that aim to address inappropriate opioid prescribing. We also performed a sensitivity analysis and an analysis in subgroups of patients with OA pain (NSAIDrefractory and those taking strong opioids only), which showed that the growing trend in future opioid burden would remain unless international recommendations on opioid use are implemented, or newer therapeutic strategies based on drugs with a novel mechanism of action replace current drug-based analgesia of chronic OA pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations